Pitching shoulder passive flexibility: torque-angle analysis for external rotation and internal rotation. Issue 8 (14th September 2022) - Wight, Jeff T.; Tillman, Mark D.; Grover, Guy B.; Chow, John W.; Borsa, Paul A.; Wikstrom, Erik A.; Larkin-Kaiser, Kelly
ABSTRACT: In this study, a custom device was developed to analyse the pitching shoulder's external rotation (ER) and internal rotation (IR) passive flexibility. We analysed three novel measures: the resistance onset angle (ROA = angle where the shoulder begins stretching), rotational stiffness, and torque at the end range of motion (ROM). The purpose was to conduct a bilateral analysis to determine if there are significant differences between the throwing and non-throwing shoulder. Participants were 30 upper level pitchers (13 division I, 17 minor league). During testing, pitchers laid supine on a treatment table and the arm was secured to a rotational wheel with the shoulder abducted 90° and elbow flexed 90°. Dependent t-tests revealed significant (p < 0.01) and relatively extreme bilateral differences for all three variables. The throwing shoulder had: increased ER ROA (9°), decreased IR ROA (5.3°), increased ER stiffness (17%), increased IR stiffness (34%), increased ER torque (21%), and increased IR torque (30%). Secondary correlation analysis was completed to determine if the torque-angle variables were good predictors of the end ROM. Stiffness correlations were weak for ER (r = 0.35, p = 0.048) and IR (r = 0.42, p = 0.017) but ROA correlations were strong for ER (r = 0.85, p < 0.001) and IR (r = 0.86, p < 0.001).